2011
DOI: 10.1074/jbc.m111.235028
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Epigenetic and Genetic Marks Are Seen in Myelodysplastic Leukocytes and Reveal Dock4 as a Candidate Pathogenic Gene on Chromosome 7q

Abstract: Myelodysplastic syndromes (MDS) are characterized by abnormal and dysplastic maturation of all blood lineages. Even though epigenetic alterations have been seen in MDS marrow progenitors, very little is known about the molecular alterations in dysplastic peripheral blood cells. We analyzed the methylome of MDS leukocytes by the HELP assay and determined that it was globally distinct from age-matched controls and was characterized by numerous novel, aberrant hypermethylated marks that were located mainly outsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 44 publications
0
42
0
Order By: Relevance
“…S5J). Our earlier work had shown that DOCK4 can also be epigenetically silenced by aberrant DNA methylation in MDS (8). We examined MDS bone marrow samples without deletion of chromosome 7 and determined that reduced expression of DOCK4 can be seen in some samples and that this result correlates with actin filament disruption seen in erythroid cells generated from these samples (SI Appendix, Fig.…”
Section: Dock4 Knockdown In Primary Human Erythroblasts Results Inmentioning
confidence: 99%
See 1 more Smart Citation
“…S5J). Our earlier work had shown that DOCK4 can also be epigenetically silenced by aberrant DNA methylation in MDS (8). We examined MDS bone marrow samples without deletion of chromosome 7 and determined that reduced expression of DOCK4 can be seen in some samples and that this result correlates with actin filament disruption seen in erythroid cells generated from these samples (SI Appendix, Fig.…”
Section: Dock4 Knockdown In Primary Human Erythroblasts Results Inmentioning
confidence: 99%
“…In a previous study (8), we had observed that numerous 7q genes, including dedicator of cytokinesis 4 (DOCK4), were deleted or epigenetically silenced in MDS, thus prompting an examination of its role in erythropoiesis in the present study. DOCK4 belongs to a large family of proteins (CED5/DOCK180/MYOBLAST CITY class) that is well conserved in mammals (9)(10)(11).…”
mentioning
confidence: 99%
“…Methylation analysis by the HELP assay (22,(57)(58)(59) and a modified protocol to successfully work with low genomic DNA yield from low numbers of sorted stem and progenitor cells have been described (24,25). Integrity of genomic DNA of high molecular weight was assured by electrophoresis for all samples used.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22] In an early study of ours, we identified disease-specific dysregulated genes and pathways using GeneChip analysis of bulk CD34 1 hematopoietic stem (HSCs) and progenitor cells (HSPCs) from patients with MDS with monosomy 7. 20 However, the absence of specific cell-membrane markers to separate cytogenetically normal and abnormal cells hindered further analysis of dysregulated molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%